REVISITING AN OLD FRIEND: WHAT CONSTITUTES “A MATTER OF MUTUAL INTEREST” IN RELATION TO A STRIKE? A TALE OF TWO RECENT CASES Pikitup (SOC) Ltd v SA Municipal Workers Union on behalf of Members (2014) 35 ILJ 983 (LAC); and Vanachem Vanadium Products (Pty) - Monray Marsellus Botha (Obiter, 2015)
The purpose of the Labour Relations Act 66 of 1995 (the LRA) is to advance economic development, social justice, labour peace and democratization of the workplace. The primary objects of the LRA, inter alia, include the following: “to provide a framework within which employees and their trade unions, employers and employer’s organisations can (i) collectively bargain to determine wages, terms and conditions of employment, and other matters of mutual interest; and (ii) formulate industrial policy”, and “to promote orderly collective bargaining [and] (ii) collective bargaining at sectoral level”. The LRA in its purpose provision also makes provision for the advancement of the effective resolution of labour disputes and employee participation in decision-making in the workplace. Central to collective bargaining is the right to strike and the recourse to lock-out, respectively available to employees and employers. The collective-bargaining system has since 2007 become increasingly adversarial as “a decline in negotiating capacity, the re-emergence of non-workplace issues negotiations, and the rise of general mistrust between the parties” as the key factors contributing to the worsening of the collective bargaining is evident. The focus on strikes, has unfortunately, not been positive, as some industries have been plagued by violent, and/or unprotected and sometimes protected strike action that carries on for long periods of time. The focus of this case note is, however, not to look at the latter categories of strikes but rather to discuss a very contentious issue related to strike action: What constitutes mutual interest with reference to strikes? Two recent cases (Pikitup (SOC) Ltd v SA Municipal Workers Union on behalf of Members (2014) 35 ILJ 983 (LAC); and Vanachem Vanadium Products (Pty) Ltd v National Union of Metal Workers of SA Case No J 658/14) will be evaluated against the backdrop of existing literature and case law on this issue.